2007
DOI: 10.1158/0008-5472.can-06-1898
|View full text |Cite
|
Sign up to set email alerts
|

ErbB-2 Induces the Cyclin D1 Gene in Prostate Epithelial Cells In vitro and In vivo

Abstract: The receptor tyrosine kinase ErbB-2 plays an important role in the regulation of growth factor-induced signal transduction cascades in the epithelium, and ErbB-2 is frequently overexpressed in epithelial tumors. Our previous studies on clinical prostate cancer specimens indicated that ErbB-2 expression was increased in patients undergoing hormone ablation therapy. We had also shown that the critical cell cycle regulatory gene cyclin D1 and its promoter were targets of proliferative signaling in prostate cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
64
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(67 citation statements)
references
References 48 publications
(63 reference statements)
2
64
0
Order By: Relevance
“…3,17 Briefly the minimal rat probasin promoter was used to drive prostate-specific expression of an activated ErbB-2 growth factor receptor. 3,17 The pten ϩ/Ϫ mice, which harbor hemizygous inactivation of one pten allele and PB-CRE ϫ Pten PC1 mice, which delete both pten alleles in the prostate epithelium as previously reported 13,18 were kindly provided by Dr. Pier Paolo Pandolfi, Memorial Sloan-Kettering Cancer Center/Beth Israel Deaconess Medical Center. The compound-engineered PB-ErbB-2 ϫ pten ϩ/Ϫ mice in an FVBN background resulted from the repeated cross-breeding of the Pten ϩ/Ϫ mice into the PB-ErbB-2 line for six or more generations.…”
Section: Generation Of Compound Animals Usedmentioning
confidence: 99%
See 3 more Smart Citations
“…3,17 Briefly the minimal rat probasin promoter was used to drive prostate-specific expression of an activated ErbB-2 growth factor receptor. 3,17 The pten ϩ/Ϫ mice, which harbor hemizygous inactivation of one pten allele and PB-CRE ϫ Pten PC1 mice, which delete both pten alleles in the prostate epithelium as previously reported 13,18 were kindly provided by Dr. Pier Paolo Pandolfi, Memorial Sloan-Kettering Cancer Center/Beth Israel Deaconess Medical Center. The compound-engineered PB-ErbB-2 ϫ pten ϩ/Ϫ mice in an FVBN background resulted from the repeated cross-breeding of the Pten ϩ/Ϫ mice into the PB-ErbB-2 line for six or more generations.…”
Section: Generation Of Compound Animals Usedmentioning
confidence: 99%
“…1,2 In previous studies, we established that increased ErbB-2 membrane expression correlated with increased nuclear cyclin D1 staining in clinical PCa specimens. 3 We also established in human PCa cell lines that ErbB-2 induced both cell cycle proliferation and cyclin D1, and that small interfering RNA targeting cyclin D1 blocked a significant proportion of the ErbB-2 or heregulin-induced cell cycle progression. Furthermore, we established that probasin-driven ErbB-2 transgene mice (PB-ErbB-2) presented with high-grade prostate intraepithelial neoplasia, (PIN), a localized adenoma, and induced epithelial cyclin D1 expression; transformation to adenocarcinoma was not observed.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…It stimulates cell differentiation and proliferation through the ligand binding to the extracellular domain. Some recent studies indicated that HER-2 stimulates AKT pathway or cyclin D1 and prolongs life or activates growth of PC cells, inhibiting apoptosis (28)(29)(30).…”
Section: ------------------------------------------------------------mentioning
confidence: 99%